PENGEMBANGAN BAHAN AJAR GAMIFIKASI PADA MATERI BANGUN RUANG SISI LENGKUNG - Farida Farida; Yoraida Khoirunnisa; Rizki Wahyu Yunian Putra (Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this study is to determine the feasibility of gamifikasi teaching materials and to determine the response of students and teachers to the developed teaching materials. The material developed in this research is to build a curved side room. Teaching materials is a primary requirement for teaching and learning process. The method in this research is research and development (R & D) with Brog and Gall development model that has been modified by Sugiyono. There are 7 stages in this development that are potential and problems, data collection, product design, product validation, product revision, product trial and product revision. The data collection instruments used are questionnaires given to material experts, media experts and linguists to determine the feasibility of the products, and are given to students and teachers to find out the attractiveness of the products that have been developed. Based on data analysis obtained from material experts, media experts and linguists it is stated that the developed teaching material is feasible to be used, and analysis of data obtained from students and teachers stated that the developed teaching material is very interesting. This means that the materials developed by researchers can be used as a learning resource for students and teachers of SMP / MTs class IX. Keywords: Gamification Teaching Materials